2013
DOI: 10.1021/cs400985m
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Transition-Metal-Catalyzed C–S Activation: From Thioester to (Hetero)aryl Thioether

Abstract: Carbon–sulfur bonds widely exist in natural products, pesticides, and drugs, and their activation, cleavage, and transformation via transition metal catalysis have become more and more important in organic chemistry. During the past several decades, great progress on transition-metal catalyzed carbon–sulfur activation of thioesters and their transformations has been achieved. Carbon–sulfur bonds linking to both heteroaryl and aryl groups can be cleaved to construct carbon–carbon bonds by coupling reactions or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(89 citation statements)
references
References 104 publications
1
85
1
2
Order By: Relevance
“…It was envisioned that the required C–H activation of the 2′-position in 1 could be achieved by a sulfur-directed cyclometallation process 11,12. With this in mind, we focused our initial effort on the development of suitable conditions for this unprecedented cyclization process involving C–S activation 9. After several experiments, we found that Pd(OAc) 2 performed as a potential catalyst for the cyclization of 1a (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was envisioned that the required C–H activation of the 2′-position in 1 could be achieved by a sulfur-directed cyclometallation process 11,12. With this in mind, we focused our initial effort on the development of suitable conditions for this unprecedented cyclization process involving C–S activation 9. After several experiments, we found that Pd(OAc) 2 performed as a potential catalyst for the cyclization of 1a (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we report a unique C–H/C–S coupling strategy for the catalytic synthesis of fused thiophene derivatives (Scheme 1d). The notable features of the reaction are as follows: (1) it does not require any reactive functionalities, such as C–X or S–H bonds; (2) it does not require an external oxidant, such as a silver salt; and (3) the reaction proceeds through the cleavage of inert C–H and C–S bonds 9. Although strong acid-mediated reaction of biphenyl sulfoxides was reported to form dibenzothiophenes through formal C–H and S–Me cleavage, its mechanism involves classical Friedel–Crafts type C–H functionalization and S–Me cleavage via the S N 2 mechanism 10…”
Section: Introductionmentioning
confidence: 99%
“…[135] Demgegenüber sind Metathesereaktionen mit aromatischen Thioestern selten, ungeachtet ihrer weiten Verbreitung in den Molekularwissenschaften. [137] Ein Metatheseprozess,indem einer der Substituenten gegen einen anderen ausgetauscht werden kann, wäre komplementärz uK reuzkupplungsmethoden, da er eine einfache Diversifikation der Thioether ermçglichen würde.E sg ab vereinzelte Berichte über C-S-Metathesereaktionen, [138] aber die erste allgemeine Methode wurde 2017 von der Gruppe um Morandi publiziert. [137] Ein Metatheseprozess,indem einer der Substituenten gegen einen anderen ausgetauscht werden kann, wäre komplementärz uK reuzkupplungsmethoden, da er eine einfache Diversifikation der Thioether ermçglichen würde.E sg ab vereinzelte Berichte über C-S-Metathesereaktionen, [138] aber die erste allgemeine Methode wurde 2017 von der Gruppe um Morandi publiziert.…”
Section: Angewandte Chemieunclassified
“…Workup of the reaction resulted in a red brown oil (0.3359g, 86%). 1 Phenyl (3-(styrylthio)propyl)sulfane (9). The title compound was prepared using the general procedure with bromobenzene (0.104 mL, 1.0 mmol).…”
Section: Scheme 4 Control Experimentsmentioning
confidence: 99%